2009
DOI: 10.1007/s11738-009-0324-1
|View full text |Cite
|
Sign up to set email alerts
|

Sodium transport in basil

Abstract: In order to diversify the production of plants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
2
7
2
3
Order By: Relevance
“…from the leaves. Similar results were obtained by Attia et al (2009) and according to these authors O. basilicum may operate an efficient mechanism of Na ? retranslocation from the shoots to the roots coupled with a desalinization mechanism of the xylem sap along the stem.…”
Section: Naclsupporting
confidence: 89%
“…from the leaves. Similar results were obtained by Attia et al (2009) and according to these authors O. basilicum may operate an efficient mechanism of Na ? retranslocation from the shoots to the roots coupled with a desalinization mechanism of the xylem sap along the stem.…”
Section: Naclsupporting
confidence: 89%
“…accumulation in stem tissues remained relatively low. In a previous work (Attia et al 2009a), we showed that a fraction of Na ? transported by the xylem sap was redirected towards the roots, revealing a desalinization mechanism of the xylem sap along the stem, which offered a supplementary protection against excessive accumulation in aerial organs.…”
Section: Discussionmentioning
confidence: 83%
“…Similar results were obtained by Attia et al . () according to whom O . basilicum may operate an efficient mechanism of Na + retranslocation from the shoots to the roots coupled with a desalinization mechanism of the xylem sap along the stem.…”
Section: Discussionmentioning
confidence: 99%
“…Basil ( Ocimum basilicum L., Lamiaceae ) is an important commercial and medicinal plant widespread in Asia, Africa, South America and in the Mediterranean region where soils and ground water are dominated by chloride and sulphate salts. This species is moderately tolerant to salt stress and differences in its response to salinity have been previously observed among different cultivars (Attia et al ., , ). Although previous studies (Tarchoune et al ., , ), performed on basil exposed to Na 2 SO 4 or NaCl excess, demonstrated that the contents of ascorbate and glutathione as well as the activities of APX, glutathione reductase and peroxidases were finely regulated by the type of salt and the cultivar sensitivity to stress, information on the role of tocopherols and lipoic acid as well as of SOD and CAT in the response of basil to different type of salts is still scanty.…”
Section: Introductionmentioning
confidence: 99%